Correlating the electron-donating core structure with morphology and performance of carbonoxygen-bridged ladder-type non-fullerene acceptor based organic solar cells. (July 2019) - Li, Wei; Xiao, Zuo; Cai, Jinlong; Smith, Joel A.; Spooner, Emma L.K.; Kilbride, Rachel C.; Game, Onkar S.; Meng, Xianyi; Li, Donghui; Zhang, Huijun; Chen, Mengxue; Gurney, Robert S.; et al.
Abstract: The chemical structure of non-fullerene acceptors (NFAs) affects their light-harvesting capabilities, energy levels and molecular orders, all of which play a crucial role in determining the efficiency of organic solar cells (OSCs). In this work, we have systematically investigated a series of ladder-type NFAs having different carbon-oxygen-bridged electron-donating cores, and revealed the effects of core structures and film casting conditions on molecular ordering and performance of OSCs. We found that NFAs containing the thieno [3, 2-b]thiophene centered, 6 or 8 fused rings (i.e. CO i 6DFIC, CO i 8DFIC) exhibit narrower optical band gaps than NFAs containing the benzene centered, 5 or 7 fused rings (i.e. CO i 5DFIC, CO i 7DFIC). NFAs containing less fused rings in the carbon-oxygen-bridged core (i.e. CO i 5DFIC and CO i 6DFIC) exhibit edge-on molecular orientation in the blends with face-on oriented PTB7-Th donor, and result in low device efficiency. Although NFAs containing more fused rings (i.e. CO i 7DFIC and CO i 8DFIC) possess a pronounced flat-on lamellar crystalline structure in the pure state, the crystallization can be reduced when blending with PTB7-Th and under hot-substrate casting, while the lamella in CO i 8DFIC can be effectively suppressed to form face-on H- and J-type aggregates, leading to enhanced efficiency. Graphical abstract: The effects of core structures and film casting conditions on molecular ordering and performance of OSCs based on a series of ladder-type NFAs are studied here. The lamellar crystallization of NFAs was suppressed and converted into H and J-type π-π stacks by blending with the donor and heating induced aggregation. Image 1 Highlights: Core structures of NFAs and film casting conditions dominate molecular ordering and performance of OSCs. Heating reduces lamellar crystals and creates more H- and J- type π-π stacks. Coexistence of H- and J- type π-π stacks broadens the light absorption.